2020
DOI: 10.3390/ijms21239090
|View full text |Cite
|
Sign up to set email alerts
|

Do TUNEL and Other Apoptosis Assays Detect Cell Death in Preclinical Studies?

Abstract: The terminal deoxynucleotidyl transferase-mediated dUTP nick end labeling (TUNEL) assay detects DNA breakage by labeling the free 3ʹ-hydroxyl termini. Given that genomic DNA breaks arise during early and late stages of apoptosis, TUNEL staining continues to be widely used as a measure of apoptotic cell death. The advantages of the assay include its relative ease of performance and the broad availability of TUNEL assay kits for various applications, such as single-cell analysis of apoptosis in cell cultures and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
86
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(89 citation statements)
references
References 74 publications
2
86
1
Order By: Relevance
“…Terminal deoxynucleotidyl transferase-mediated dUTP nick end labeling (TUNEL) assay was used to detect DNA fragmentation by labeling the free 3’- hydroxy terminal. In short, TUNEL is a method of staining cells by labeling broken DNA, which is often used to determine cells in the early stage of apoptosis Mirzayans and Murray ( 2020 ). To further demonstrate the association among oxidative stress, mitochondria, and apoptosis, we also measured the mitochondrial membrane potential and TUNEL-positive cells in testes.…”
Section: Discussionmentioning
confidence: 99%
“…Terminal deoxynucleotidyl transferase-mediated dUTP nick end labeling (TUNEL) assay was used to detect DNA fragmentation by labeling the free 3’- hydroxy terminal. In short, TUNEL is a method of staining cells by labeling broken DNA, which is often used to determine cells in the early stage of apoptosis Mirzayans and Murray ( 2020 ). To further demonstrate the association among oxidative stress, mitochondria, and apoptosis, we also measured the mitochondrial membrane potential and TUNEL-positive cells in testes.…”
Section: Discussionmentioning
confidence: 99%
“…During the early and late stages of apoptosis, genomic DNA breaks arise. So TUNEL staining is widely used as a measure of apoptosis, and TUNEL-positive cells are a specific parameter that indicates the apoptotic cells [ 36 ]. As shown in Figure 8 , L-Glu treatment significantly increased the number of TUNEL-positive cells (red fluorescence-labeled cells) as compared with control SH-SY5Y cells, indicating that L-Glu (30 mmol/L) promoted the apoptosis of SH-SY5Y cells.…”
Section: Resultsmentioning
confidence: 99%
“…Our ex vivo study demonstrated that the number of TUNEL-positive epidermal cells increased after UVB irradiation, whereas subsequent FMR treatment decreased their numbers ( Figure 4 , p < 0.005). Stress-induced premature senescence is a genetically controlled process, mediated by p16 and p21, depending on the cellular p53 status [ 14 ]. Additional quantitative reverse transcription–polymerase chain reaction (qRT–PCR) revealed that the mRNA expression levels of not only p16, p21, and p53, but also of matrix metalloproteinase (MMP)-2 and MMP-9 significantly increased after UVB exposure.…”
Section: Resultsmentioning
confidence: 99%